Numerical Study of a Single-Sided Vibro-Impact Track Nonlinear Energy Sink Considering Horizontal and Vertical Dynamics - Li, Wenke; Wierschem, Nicholas E.; Li, Xinhui; Yang, Tiejun; Brennan, Michael J. [UNESP] (Asme, 2019)
In this paper, the single-sided vibro-impact track nonlinear energy sink (SSVI track NES) is studied. The SSVI track NES, which is attached to a primary structure, has nonlinear behavior caused by the NES mass moving on a fixed track and impacting on the primary structure at an impact surface. Unlike previous studies of the SSVI track NES, both the horizontal and vertical dynamics of the primary structure are considered. A numerical study is carried out to investigate the way in which energy is dissipated in this system. Assuming a track shape with a quartic polynomial, an optimization procedure that considers the total energy dissipated during a time period is carried out, to determine the optimum NES mass and track parameter. It is found that there is dynamic coupling between the horizontal and vertical directions caused by the SSVI track NES motion. The vibrational energy, originally in the structure in the horizontal direction, is transferred to the vertical motion of the structure where it is dissipated. Considering that many civil and mechanical systems are particularly vulnerable to extreme loads in the horizontal direction, this energy transformation can be beneficial to prevent or limit damage to the structure. The effect on energy dissipation of the position of the impact surface in the SSVI track NES and the ratio of the vertical to horizontal stiffness in the primary structure are discussed. Numerical results demonstrate a robust and stable performance of the SSVI track NES over a wide range of stiffness ratios.
Keywords: nonlinear energy sink; passive control; vibration mitigation; impact damper; structural dynamics and control; vibration control